Female genital mutilation as sexual disability:perceptions of women and their spouses in Akure,Ondo State, Nigeria (2017)
Disability encompasses the limitations on an individual’s basic physical activities, and the consequent social oppressions such individual faces in society. In this regard, the limitation on the use of some parts of the genitals in a patriarchal system is considered a form of disability. This paper describes the perceptions of and the coping mechanisms employed by affected couples dealing with the consequences of female genital mutilation (FGM) as a form of sexual disability. Cultural Libertarianism was employed as a theoretical framework. The paper presents the results of a descriptive cross-sectional study conducted in Akure, Ondo State, Nigeria, with 10 male and 12 female respondents purposively selected through a snowball sampling for in-depth interviews. The findings present the justifications provided for the practice of FGM, and victims’ perceptions of how it affects their sexual relations. Furthermore, it highlights coping strategies employed by affected women and their spouses. The study shows that the disabling consequence of FGM is largely sexual in nature, leading to traumatic experiences and negative beliefs about sex, and requiring a myriad of coping strategies employed by the disabled women, and their spouses, which may have its own implications for marital and sexual bliss.